2021
DOI: 10.1038/s41598-021-92456-w
|View full text |Cite
|
Sign up to set email alerts
|

Anethole induces anti-oral cancer activity by triggering apoptosis, autophagy and oxidative stress and by modulation of multiple signaling pathways

Abstract: Oral cancer is one of the major public health problems. The aim of this study was to evaluate the effects of anethole, 1-methoxy-4-[(E)-1-propenyl]-benzene, on growth and apoptosis of oral tumor cells, and to identify the signaling pathways involved in its interaction with these cancer cells. Cancer gingival cells (Ca9-22) were treated with different concentrations of anethole. Cell proliferation and cytotoxic effects were measured by MTT and LDH assays. Cell death, autophagy and oxidative stress markers were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 44 publications
3
31
0
Order By: Relevance
“…In our study all of the oxidative stress markers were significantly elevated as compared to healthy individual. Similarly, results were noted by K Babiuchet al and many other researchers (Babiuch et al, 2019;Bozan et al, 2018;Cherian et al, 2019;Contant et al, 2021). Interlukin-6 is a multifunctional cytokine having a wide range of immunological activities, and it is also a potential mediator in the cancer development.…”
Section: Resultssupporting
confidence: 69%
“…In our study all of the oxidative stress markers were significantly elevated as compared to healthy individual. Similarly, results were noted by K Babiuchet al and many other researchers (Babiuch et al, 2019;Bozan et al, 2018;Cherian et al, 2019;Contant et al, 2021). Interlukin-6 is a multifunctional cytokine having a wide range of immunological activities, and it is also a potential mediator in the cancer development.…”
Section: Resultssupporting
confidence: 69%
“…The human oral cancer cell line Ca9–22 cells were cultured at 37 °C and 5% CO 2 in RPMI-1640 medium (Thermo Fisher Scientific, Burlington, ON, Canada), supplemented with L-glutamine, 5% fetal bovine serum (FBS, Gibco) provided by the same company, and 1% penicillin/streptomycin solution (Sigma-Aldrich, Oakville, ON, Canada). Cell proliferation was bi-evaluated using two MTT and LDH tests as described by Semlali et al 2021 [ 35 , 36 ] and Contant et al 2021 [ 37 ]. For the MTT assay, 10 5 Ca9-22 cells per well containing the sample were seeded in 24-well plates for 24 h. After adhesion and growth of the cells, the culture medium is replaced by a new one containing a solution of MTT at 5 mg∙ml −1 in PBS and left for 3 h at 37 °C in the dark.…”
Section: Methodsmentioning
confidence: 99%
“…Examples of phenylpropanoids such as anethole, cinnamaldehyde, eugenol, isoeugenol, myristicin, safrole, and vanillin. In a recent study, anethole has been reported to yield anticancer activity ( Contant, Rouabhia, Loubaki, Chandad, & Semlali, 2021 ). Moreover, myristicin has been described to exert antiproliferative and anti-inflammatory properties ( Seneme, Dos Santos, Silva, Franco, & Longato, 2021 ) and safrole has been reported to promote diverse biological activities, such as antidiabetic, antimicrobial, analgesic, and antifungal activities ( Eid & Hawash, 2021 ).…”
Section: Bioactive Compounds Of Essential Oilsmentioning
confidence: 99%